Male weasels decrease activity and energy expenditure in response to high ambient temperatures. - Karol Zub (Public Library of Science (PLoS), 2013)
The heat dissipation limit (HDL) hypothesis suggests that the capacity of endotherms to dissipate body heat may impose constraints on their energy expenditure. Specifically, this hypothesis predicts that endotherms should avoid the detrimental consequences of hyperthermia by lowering their energy expenditure and reducing their activity in response to high ambient temperatures (T(a)). We used an extensive data set on the daily energy expenditure (DEE, n = 27) and the daily activity time (AT, n = 48) of male weasels (Mustela nivalis) during the spring and summer breeding season to test these predictions. We found that T(a) was related in a "hump-shaped" (i.e. convex) manner to AT, DEE, resting metabolic rate (RMR) and metabolic scope (the ratio of DEE to RMR). These results support the HDL hypothesis because in response to warm Tas male weasels reduced their AT, DEE, and RMR. Although the activity and energy expenditure of large endotherms are most likely to be constrained in response to warm Tas because they are less able to dissipate heat, our results suggest that small endotherms may also experience constraints consistent with the HDL hypothesis.